The effectiveness of English secondary schools for pupils of different ability levels - Lorraine Dearden; John Micklewright; Anna Vignoles (Institute for the Study of Labor (IZA), 2011)
League table information on school effectiveness in England generally relies on either a comparison of the average outcomes of pupils by school, e.g. mean exam scores, or on estimates of the average value added by each school. These approaches assume that the information parents and policy-makers need most to judge school effectiveness is the average achievement level or gain in a particular school. Yet schools can be differentially effective for children with differing levels of prior attainment. We present evidence on the extent of differential effectiveness in English secondary schools, and find that even the most conservative estimate suggests that around one quarter of schools in England are differentially effective for students of differing prior ability levels. This affects an even larger proportion of children as larger schools are more likely to be differentially effect.
urn:nbn:de:101:1-201107283627
Keywords: I2; 330; school effectiveness; school choice; value added; England